Taxanes in the neoadjuvant treatment of operable and locally advanced breast cancer - Suszko-Każarnowicz, Małgorzata; Ryniewicz-Zander, Iwona (Contemporary Oncology/Współczesna Onkologia, 2004)
Breast cancer is the most common malignant tumor among women. Preoperational chemotherapy is the standard procedure in treating changes of a locally advanced breast cancer and inflammatory cancer. Neoadjuvant treatment is more often used in the early stages of breast cancer. Nevertheless, there are not many advantages of this procedure. The response to neoadjuvant chemotherapy may be used as a chemosensitivity test. Many randomized trials of phase II were carried out. In those trials taxanes’ effectiveness and toxicity were estimated in monotherapy, in combination with one or more pharmaceuticals and in schemes with a dose-dense. In the majority of trials many clinical and pathological responses with acceptable treatment toxicity were obtained. In schemes with a dose-dense there was a necessity of prophylactic use of a growth factor and an antibiotic. Three trials of the phase II/III were completed which assessed the effect of taxanes on the frequency full pathological responses and on life expectancy in neoadjuvant treatment. Early data from a randomized trial from Aberdeen suggest that the total pathological remission obtained in neoadjuvant treatment may reflect the longer life expectancy of the patients. Long-lasting involvement of axillary lymph nodes (in the microscopic examination) is a disadvantageous prognostic factor. Treatment schemes combining docetaxel with doxorubicin increase clinical and pathological responses.